Game changers for meat and masculinity? Male athletes’ perspectives on mixed and plant-based diets - van der Horst, Hilje; Sällylä, Annie; Michielsen, Yolie (Appetite, 2023)
The dietary choices of male athletes are increasingly a topic of moral and nutritional debate. Though it has long been a consensus that athletes require animal products to advance their athletic goals, this understanding is now challenged in academic and popular sources based on nutritional evidence and concern about the environmental impacts of animal products. In order to better understand how (semi-)professional male athletes perceive plant-based diets and diets containing animal products, thirteen semi-structured interviews were conducted with male athletes competing nationally and internationally, including mixed and plant-based eaters. Interviews were analysed through reflexive thematic analysis, in line with a critical, qualitative research methodology. Justifications for meat, situated knowledge and masculinity were used as theoretical lenses. Our analysis shows how athletes reproduce nutritional claims about the necessity of protein for athletes, but disagree on the suitability of plant-based sources. This nutritional discourse derives from a broad range of sources, including professional nutritionists, friends, online influencers, and media. Second, when explaining their own food practices, food being ‘nice’ and ‘normal’ – common justifications for meat as evidenced in the 4N theory – often supersede necessity. Embedding these views in their everyday lives as athletes shows that food environments and shared eating practices fortify a mixed diet as normal, and plant-based diets as anomalous. It further shows how the view of meat being normal is subject to shifting masculinity norms. Interviewees reject meat eating as normal and masculine for men, while male athletes who show dedication, constraint, and knowledge in a plant-based diet are viewed positively. As role models for diet and masculinity, this has implications for a potential role of athletes in a societal transition towards lower consumption of animal products.